La metafisica dell’Uno di Piero Martinetti come pensiero orante (Materiali di Estetica. Terza serie, 2019)
The paper intends to show how religious inspiration informs Martinetti's metaphysics, which has its center in the Absolute, conceived as One in its expression, both intelligible and sensitive, conceived outside any dualism. In Martinetti's philosophy the One is the highest name of God, because he expresses both his radical transcendence and his being as gathering what is essential to the events of the human route.